Analysis of New Student Admission Application for Bina Warga High School in Palembang - Helda, Yudiastuti; Misinem, . (INTI International University, 2024)
The manual admission process at Bina Warga 2 High School Palembang poses significant challenges, including inefficiencies in registration, limited accessibility for prospective students, and increased administrative workload. To address these issues, this study analyses the requirements for an online student admission system designed to streamline registration, facilitate efficient report generation, and serve as a promotional platform for the school. By adopting the Prototyping method for system development, the process ensures active collaboration between developers and stakeholders, enabling iterative refinement based on user feedback. The proposed system eliminates the need for prospective students to visit the school physically, thereby enhancing accessibility and scalability. Furthermore, it automates administrative tasks, reducing manual effort and improving overall efficiency. This analysis highlights the potential of an online admission system to transform the registration process, expand the school’s outreach, and establish a robust digital presence for future growth.